A copper-containing silicon-carbon negative electrode material, preparation method thereof and lithium-ion battery

By depositing copper film layers and silicon particles on the porous carbon frame material, forming copper-containing silicon carbon negative electrode materials, the problems of volume expansion and insufficient conductivity are solved, and a lithium-ion battery with high capacity retention and fast charging capabilities are achieved.

CN119307881BActive Publication Date: 2025-04-29安徽得壹能源科技有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411822770.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-29
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

In the prior art, the volume expansion problem of copper-containing silicon-carbon materials is serious, the capacity retention rate is low under long-term cycles, and the preparation method is high, making it difficult to mass production on a large scale.

Method used

Chemical vapor deposition method is used to deposit copper film layers on the surface of porous carbon frame material to form a continuous conductive network, and silicon particles are deposited on the copper cladding layer, controlling the mass fraction of silicon between 20 and 50 wt%.

Benefits of technology

It achieves good conductivity of the material, improves the fast charging capability and cycle life of the battery. In the charge and discharge cycle test of 25℃, 1C/1C, the capacity retention rate reaches more than 90%, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307881B_ABST
    Figure CN119307881B_ABST
Patent Text Reader

Abstract

The present invention discloses a copper-containing silicon-carbon negative electrode material, a preparation method thereof and a lithium-ion battery, and belongs to the technical field of lithium-ion battery electrode materials. The preparation method provided by the present invention comprises the following steps: chemical vapor deposition is performed on the surface of a porous carbon skeleton material using a copper source, the thickness of the copper deposition layer is controlled to be 2-200 nm, and then annealing is performed to obtain a copper-coated porous carbon skeleton material; chemical vapor deposition is performed on the surface of the copper-coated porous carbon skeleton material using a silicon source to obtain a copper-containing silicon-carbon negative electrode material; in the copper-containing silicon-carbon negative electrode material, the mass fraction of silicon is 20-50wt%. The present invention adopts a two-step chemical vapor deposition method, the overall preparation process is simple, the process is stable, and it is suitable for large-scale production; the obtained copper-containing silicon-carbon negative electrode material has good fast charging performance and cycle performance when used in lithium-ion batteries. In the charge and discharge cycle test at 25°C and 1C / 1C, the capacity retention rate after 500 cycles is above 90%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery electrode materials, and in particular to a copper-containing silicon-carbon negative electrode material, a preparation method thereof and a lithium ion battery. Background Art

[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] As battery technology gradually develops towards high energy density, graphite anodes have gradually been unable to meet the demand for gram capacity. Its theoretical gram capacity is relatively low and the current commercialized graphite has gradually reached its design limit. In recent years, silicon anodes have received widespread attention due to their ultra-high gram capacity (4200mAh / g). However, during the charging and discharging process of silicon anode materials, the lithium insertion and delithiation process will cause serious volume changes in silicon materials. As a result, silicon particles are prone to pulverization and powder loss during long-term cycles, resulting in deterioration of cycle performance. At the same time, silicon materials are semiconductors with poor conductivity, and the fast charging capability of silicon anode batteries needs to be improved. Therefore, a lot of research work is focused on improving the cycle performance, fast charging capability and volume expansion phenomenon of silicon anodes.

[0004] The patent with publication number CN117059768A discloses a copper-coated silicon oxide @ carbon composite material, which is carbon-coated on the surface of silicon oxide and then coated with metallic copper by hydrothermal method to obtain a copper-coated silicon oxide carbon composite material. The core of the material structure is silicon oxide, and from the inside to the outside, there are carbon layers and copper coating layers. The patent adopts hydrothermal method to coat metallic copper, which is costly and difficult to mass produce on a large scale. Moreover, it adopts chemical copper plating method, and there is great uncertainty in the purity and density of metallic copper. The patent with publication number CN104979559A discloses a method for preparing nano-copper particles coated with nano-silicon particles. The method is to acid-etch silicon particles, form a pore structure on the surface of silicon particles, and then disperse porous silicon particles in copper plating solution, and prepare copper-coated nano-silicon composite materials by chemical copper plating. The copper in this method exists in the form of dispersed particles, and no continuous conductive network is formed, and the conductivity is not improved enough. The volume expansion problem of the copper-containing silicon-carbon material produced by the above-mentioned patent is still relatively serious, the capacity retention rate under long-term cycling is low, and the capacity decay is relatively fast.

[0005] Therefore, how to prepare a copper-containing silicon-carbon composite material with good electrical conductivity and less obvious volume expansion by a low-cost and simple method is an urgent problem to be solved. Summary of the invention

[0006] In view of this, the present invention provides a copper-containing silicon-carbon negative electrode material, a preparation method thereof and a lithium-ion battery. The copper-containing silicon-carbon negative electrode material prepared by the present invention can form a continuous conductive network, the material has good conductivity, and the capacity retention rate under a long cycle test is high. At the same time, the preparation method is relatively simple and can be mass-produced.

[0007] In a first aspect, the present invention provides a method for preparing a copper-containing silicon-carbon negative electrode material, comprising the following steps:

[0008] Chemical vapor deposition is performed on the surface of the porous carbon skeleton material using a copper source, the thickness of the copper deposition layer is controlled to be 2-200 nm, and then annealing is performed to obtain a copper-coated porous carbon skeleton material;

[0009] Chemical vapor deposition is performed on the surface of a copper-coated porous carbon skeleton material using a silicon source to obtain a copper-containing silicon-carbon negative electrode material; in the copper-containing silicon-carbon negative electrode material, the mass fraction of silicon is 20-50wt%.

[0010] In a second aspect, the present invention provides a copper-containing silicon-carbon negative electrode material prepared by the above-mentioned preparation method.

[0011] In a third aspect, the present invention provides a lithium-ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte; the negative electrode comprises the above-mentioned copper-containing silicon-carbon negative electrode material.

[0012] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0013] (1) The present invention uses chemical vapor deposition to deposit a copper film layer on the surface of a porous carbon skeleton material, thereby forming a continuous conductive network on the surface of the porous carbon skeleton. The copper film is uniform and dense, has a controllable thickness, and has good conductivity, thereby greatly improving the fast charging capability of the battery.

[0014] (2) The present invention adopts a two-step chemical vapor deposition method. The process similarity of each step is high, the reaction device can be shared, the difficulty of equipment modification is low, the overall preparation process is simple, the process is stable, and it is suitable for large-scale production.

[0015] (3) In the copper-containing silicon-carbon negative electrode material obtained by the present invention, the porous structure of the porous carbon skeleton material can significantly alleviate the problem of volume expansion. At the same time, since the copper layer is completely deposited in the porous carbon skeleton structure to form a conductive film, the silicon particles are deposited on the conductive film, which can greatly improve the conductivity. In addition, copper is a metal with extremely good ductility. The copper layer can synergistically alleviate the volume expansion of the silicon particles and stabilize the negative electrode structure. Therefore, the assembled battery has a longer cycle life. In the charge and discharge cycle test at 25°C and 1C / 1C, the capacity retention rate after 500 cycles is above 90%. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0017] Figure 1 Schematic diagram of the preparation process of the copper-containing silicon-carbon negative electrode material according to Example 1 of the present invention;

[0018] Figure 2 It is a charging capacity curve diagram of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0019] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0020] The present invention provides a method for preparing a copper-containing silicon-carbon negative electrode material, comprising the following steps:

[0021] Chemical vapor deposition is performed on the surface of the porous carbon skeleton material using a copper source, the thickness of the copper deposition layer is controlled to be 2-200 nm, and then annealing is performed to obtain a copper-coated porous carbon skeleton material;

[0022] Chemical vapor deposition is performed on the surface of a copper-coated porous carbon skeleton material using a silicon source to obtain a copper-containing silicon-carbon negative electrode material; in the copper-containing silicon-carbon negative electrode material, the mass fraction of silicon is 20-50wt%.

[0023] The present invention first deposits a copper film layer in the porous structure of the porous carbon skeleton. The copper film layer is completely deposited in the porous carbon skeleton structure to form a continuous conductive network, which greatly improves the conductivity of the negative electrode material and enables the negative electrode material to have good fast charging performance. Then, silicon particles are deposited on the surface of the copper-coated porous carbon skeleton material. The presence of silicon particles can greatly increase the gram capacity of the negative electrode material. Under the combined effect of the porous structure of the porous carbon skeleton and the good ductility of the copper film layer, the volume expansion problem of the negative electrode material is effectively alleviated, so that the battery assembled with the negative electrode material has a longer cycle life.

[0024] In the present invention, the particle size of the porous carbon skeleton material is 3 to 15 μm. The present invention does not impose any special restrictions on the source of the porous carbon skeleton material, which can be obtained by carbonizing and etching pores from biomass materials (such as coconut shells, etc.), synthetic resins (such as phenolic resins or epoxy resins) or natural organic matter (such as starch, cellulose, etc.) as raw materials. The porous carbon skeleton materials obtained by the above methods are all commercially available products, and those skilled in the art can purchase them according to actual needs.

[0025] In the present invention, the copper source is selected from a copper-containing organic precursor or a copper-containing inorganic precursor; the present invention does not impose any special restrictions on the specific selection of the copper source, as long as a copper film layer can be chemically vapor deposited on the porous carbon surface. Copper-containing organic precursors include but are not limited to Cu(hfac)(TMVS), Cu(hfac)(DMB), Cu(hfac)(MP), Cu(hfac)(VTMOS), Cu(hfac)(VCH), Cu(hfac)(COD), Cu(hfac)(DMCOD), etc., and the present invention preferably uses Cu(hfac)(TMVS). Copper-containing inorganic precursors include CuCl or CuCl2, etc.

[0026] In the present invention, in the step of chemical vapor deposition using a copper source, the temperature of chemical vapor deposition is 200-900°C, and the specific temperature is determined according to the type of copper source selected. Generally speaking, the chemical vapor deposition temperature of a copper-containing organic precursor is 200-300°C, and the chemical vapor deposition temperature of a copper-containing inorganic precursor is 300-900°C. In the present invention, the time of chemical vapor deposition is 3-100 minutes, and the specific time can be determined according to the thickness. The thickness of the copper deposit layer of the present invention is preferably 5-100nm, and more preferably 5-50nm.

[0027] In the present invention, the flow rate of the gas used in the chemical vapor deposition process is 1-5 L / min, and the gas includes a vaporized copper source and a carrier gas, and the carrier gas is one or more of hydrogen, argon or nitrogen; the volume fraction of the vaporized copper source is 85-95%.

[0028] The present invention does not impose any special restrictions on the equipment for the chemical vapor deposition process. The process can be carried out in a tube furnace or in a fluidized bed, and those skilled in the art can make the selection according to actual conditions.

[0029] In the present invention, the annealing temperature is 400-500° C., and the annealing time is 20-60 minutes. A dense copper thin film layer can be obtained after annealing.

[0030] In the present invention, the silicon source is selected from monosilane, disilane or dichlorosilane, and monosilane is preferred in the present invention. The present invention does not impose any special restrictions on the equipment for chemical vapor deposition of silicon source, and it can be carried out in a tube furnace or in a fluidized bed. Those skilled in the art can choose according to actual conditions.

[0031] In the present invention, in the step of chemical vapor deposition using a silicon source, the time of chemical vapor deposition is 0.5 to 5 hours, more preferably 0.5 to 2 hours; the temperature of chemical vapor deposition is 300 to 600°C, more preferably 450 to 550°C; the flow rate of the silicon source gas is 1 to 5 L / min. The silicon content in the final negative electrode material is controlled by controlling the parameters of the chemical vapor deposition process. Although a higher silicon content can obtain a higher gram capacity, the volume expansion of silicon cannot be well alleviated during the process of lithium removal and lithium insertion, resulting in a decrease in cycle performance.

[0032] The present invention provides a copper-containing silicon-carbon negative electrode material, which is prepared by the above-mentioned preparation method. The copper-containing silicon-carbon negative electrode material of the present invention has excellent electrochemical properties, has good cycle stability when applied to lithium-ion batteries, has a capacity retention rate of more than 90% after 500 cycles under 1C / 1C charge and discharge conditions, has excellent fast charging performance, and maintains a relatively high gram capacity.

[0033] The present invention provides a lithium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte; the negative electrode comprises the above copper-containing silicon-carbon negative electrode material.

[0034] The present invention has no special restrictions on the positive electrode of the lithium-ion battery, and preferably uses NCM (nickel cobalt manganese) ternary positive electrode material as the positive electrode active material; the present invention has no special restrictions on the source of the NCM ternary positive electrode material, and commercially available products can be used.

[0035] In the present invention, the negative electrode includes the copper-containing silicon-carbon negative electrode material described in the above technical solution. The present invention does not impose any special restrictions on the preparation method of the negative electrode, and the preparation method of the silicon-carbon negative electrode commonly used in the art can be adopted. The present invention is preferably: the negative electrode active material, the binder, and the conductive agent are mixed in a mass ratio of (90~96): (2~5): (1~3) to form a slurry, which is coated on the current collector, dried, and rolled; the negative electrode active material includes the copper-containing silicon-carbon negative electrode material and graphite; the mass ratio of the copper-containing silicon-carbon negative electrode material and graphite is (5~15): (85~95).

[0036] The present invention has no special limitation on the separator of the lithium-ion battery, and any separator well known to those skilled in the art can be used. The present invention preferably uses a polyethylene separator.

[0037] The present invention has no particular limitation on the electrolyte of the lithium-ion battery. For example, a mixed solution of 1 mol / L lithium hexafluorophosphate of ethylene carbonate (EC) and dimethyl carbonate (DMC) (the volume ratio of EC to DMC is 1:1) well known to those skilled in the art can be used.

[0038] The present invention has no special limitation on the method for preparing the lithium ion battery, and any method for preparing lithium ion batteries well known to those skilled in the art may be used.

[0039] The technical solution of the present invention is further described below in conjunction with specific embodiments. The present invention has no special restrictions on the source of the reagents in the following embodiments, and commercially available products known to those skilled in the art can be used. In the following embodiments, the average particle size of the porous carbon skeleton material is 10 μm.

[0040] Example 1

[0041] This embodiment provides a method for preparing a copper-containing silicon-carbon negative electrode material. The preparation schematic diagram is shown in FIG. Figure 1 shown.

[0042] (1) Preparation of copper-coated porous carbon skeleton materials: The purchased porous carbon skeleton materials were placed in a high-temperature vacuum device. Argon was used as a carrier gas. The vaporized copper-containing organic compound (Cu(hfac)(TMVS), with a volume fraction of 90%) was introduced into the high-temperature vacuum device. At 300°C, the copper-containing organic matter decomposed and deposited in the porous carbon to form a copper thin film layer. The gas flow rate was 3 L / min and the deposition time was 5 min. The thickness of the obtained copper deposition layer was about 10 nm. After the deposition was completed, it was annealed at 450°C for 30 min to obtain a porous carbon skeleton material containing a uniform and dense copper thin film layer.

[0043] (2) Preparation of copper-containing silicon-carbon negative electrode material: The copper-coated porous carbon skeleton material obtained in step (1) is introduced into a fluidized bed device with argon as a carrier gas at a gas flow rate of 2 L / min; then monosilane gas is introduced into the fluidized bed at a monosilane flow rate of 2 L / min, the silane deposition temperature is 500°C, and the deposition time is 60 min to obtain a copper-containing silicon-carbon negative electrode material. It has been determined that the mass fraction of silicon in the copper-containing silicon-carbon negative electrode material is 48 wt%.

[0044] Example 2

[0045] This embodiment provides a method for preparing a copper-containing silicon-carbon negative electrode material.

[0046] (1) Preparation of copper-coated porous carbon skeleton materials: The purchased porous carbon skeleton materials were placed in a high-temperature vacuum device. Argon was used as a carrier gas. The vaporized copper-containing organic compound (Cu(hfac)(TMVS), with a volume fraction of 90%) was introduced into the high-temperature vacuum device. At 300°C, the copper-containing organic matter decomposed and deposited in the porous carbon to form a copper thin film layer. The gas flow rate was 3 L / min and the deposition time was 30 min. The thickness of the obtained copper deposition layer was about 30 nm. After the deposition was completed, it was annealed at 450°C for 30 min to obtain a porous carbon skeleton material containing a uniform and dense copper thin film layer.

[0047] (2) Preparation of copper-containing silicon-carbon negative electrode material: The copper-coated porous carbon skeleton material obtained in step (1) is introduced into a fluidized bed device with argon as a carrier gas at a gas flow rate of 2 L / min; then monosilane gas is introduced into the fluidized bed at a monosilane flow rate of 2 L / min, the silane deposition temperature is 500°C, and the deposition time is 60 min to obtain a copper-containing silicon-carbon negative electrode material. It is determined that the mass fraction of silicon in the copper-containing silicon-carbon negative electrode material is 47.9 wt%.

[0048] Comparative Example 1

[0049] The difference between this comparative example and Example 1 is that copper is not deposited on the surface of the porous carbon skeleton material. The specific steps are as follows:

[0050] The purchased porous carbon skeleton material was introduced into the fluidized bed equipment with argon as the carrier gas at a gas flow rate of 2 L / min; then monosilane gas was introduced into the fluidized bed with a silane flow rate of 2 L / min, a silane deposition temperature of 500°C, and a deposition time of 60 min to obtain a silicon-carbon negative electrode material.

[0051] Comparative Example 2

[0052] The difference between this comparative example and Example 1 is that the mass fraction of silicon in the copper-containing silicon-carbon negative electrode material of this comparative example is 65wt%. The specific preparation steps are as follows:

[0053] (1) Preparation of copper-coated porous carbon skeleton materials: The purchased porous carbon skeleton materials were placed in a high-temperature vacuum device. Argon was used as a carrier gas. The vaporized copper-containing organic compound (Cu(hfac)(TMVS), with a volume fraction of 90%) was introduced into the high-temperature vacuum device. At 300°C, the copper-containing organic matter decomposed and deposited in the porous carbon to form a copper thin film layer. The gas flow rate was 3 L / min and the deposition time was 5 min. The thickness of the obtained copper deposition layer was about 10 nm. After the deposition was completed, it was annealed at 450°C for 30 min to obtain a porous carbon skeleton material containing a uniform and dense copper thin film layer.

[0054] (2) Preparation of copper-containing silicon-carbon negative electrode material: The copper-coated porous carbon skeleton material obtained in step (1) is introduced into a fluidized bed device with argon as a carrier gas at a gas flow rate of 2 L / min; then monosilane gas is introduced into the fluidized bed at a monosilane flow rate of 2 L / min, the silane deposition temperature is 500°C, and the deposition time is 80 min to obtain a copper-containing silicon-carbon negative electrode material. It has been determined that the mass fraction of silicon in the copper-containing silicon-carbon negative electrode material is 65 wt%.

[0055] Comparative Example 3

[0056] The difference between this comparative example and Example 1 is that in this comparative example, silane chemical vapor deposition is performed first, and then copper chemical vapor deposition is performed. The specific steps are as follows:

[0057] (1) The purchased porous carbon skeleton material was introduced into a fluidized bed device with argon as carrier gas at a gas flow rate of 2 L / min; then monosilane gas was introduced into the fluidized bed at a silane flow rate of 2 L / min, a silane deposition temperature of 500°C, and a deposition time of 60 min to obtain a silicon-carbon composite material;

[0058] (2) Preparation of copper-coated silicon-carbon negative electrode material: The silicon-carbon composite material obtained in step (1) is placed in a high-temperature vacuum device, and argon is used as a carrier gas to introduce a vaporized copper-containing organic compound (Cu(hfac)(TMVS), with a volume fraction of 90%) into the high-temperature vacuum device. At 300°C, the copper-containing organic matter decomposes and deposits on the surface of the silicon-carbon composite material to form a copper thin film layer. The gas flow rate is 3 L / min, and the deposition time is 5 min. The thickness of the obtained copper deposition layer is about 10 nm. After the deposition is completed, it is annealed at 450°C for 30 min to obtain a copper-coated silicon-carbon negative electrode material.

[0059] Comparative Example 4

[0060] The difference between this comparative example and Example 1 is that the copper coating layer of this comparative example is realized by a hydrothermal method. The specific steps are as follows:

[0061] (1) Preparation of copper-coated porous carbon skeleton material: 0.1 mol copper nitrate, 0.5 mol ammonium bicarbonate, and 0.1 mol ascorbic acid were added to 1000 mL of deionized water, and then 200 g of porous carbon skeleton material was added. After ultrasonic treatment for 1 h, the mixture was transferred to a hydrothermal reactor and kept at 160 ° C for 8 h. After the reaction was completed, the mixture was centrifuged, washed with water, and vacuum dried at 80 ° C to obtain a copper-coated porous carbon skeleton material.

[0062] (2) Preparation of copper-containing silicon-carbon negative electrode material: The copper-coated porous carbon skeleton material obtained in step (1) is introduced into a fluidized bed device with argon as a carrier gas at a gas flow rate of 2 L / min; then monosilane gas is introduced into the fluidized bed at a monosilane flow rate of 2 L / min, the silane deposition temperature is 500°C, and the deposition time is 60 min to obtain a copper-containing silicon-carbon negative electrode material. It has been determined that the mass fraction of silicon in the copper-containing silicon-carbon negative electrode material is 47.2 wt%.

[0063] Test example

[0064] The negative electrode materials of Examples 1-2 and Comparative Examples 1-4 were assembled into batteries for electrochemical performance testing. The specific assembly process is as follows:

[0065] (1) Preparation of positive electrode sheets: Polyvinylidene fluoride (PVDF), conductive agent (SP) and positive electrode material (NCM811) are added to N-methylpyrrolidone (NMP) in a mass ratio of 1.2:1.5:97.3 in sequence, and the mixture is stirred and mixed thoroughly. The slurry is coated on the surface of the aluminum current collector, and then dried, cold pressed and punched to obtain positive electrode sheets.

[0066] (2) Preparation of negative electrode sheets: Sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber latex (SBR), conductive agent (SP) and negative electrode active material (the negative electrode active material is a mixture of commercial graphite and the negative electrode material prepared in the embodiment or comparative example in a mass ratio of 90:10) are added to deionized water in sequence in a mass ratio of 1.7:1.8:1.5:95, and the mixture is stirred and mixed evenly. The slurry is coated on a copper foil current collector, and then dried, cold pressed and punched to obtain a negative electrode sheet.

[0067] (3) The polyethylene separator and the positive electrode sheet and the negative electrode sheet prepared in step (1) and step (2) are stacked in a "Z" shape, and the battery cell to be filled with liquid is obtained by packaging with an aluminum-plastic film. After baking, an electrolyte is injected, wherein the electrolyte is a mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DMC) containing 1 mol / L lithium hexafluorophosphate, wherein the volume ratio of EC to DMC is 1:1, and a lithium-ion battery with a nominal capacity of 3 Ah to be tested is obtained.

[0068] The negative electrode materials of the embodiments and comparative examples and the assembled lithium ion batteries were subjected to the following tests:

[0069] 1. Powder resistivity test: Four-probe method test, according to the resistivity formula ρ=2πs V / I (where ρ is the resistivity, s is the probe spacing, V is the measured voltage, I is the current passing through) to calculate the resistivity of the negative electrode material.

[0070] 2. Battery internal resistance test: Use a battery internal resistance tester to test the resistance of the battery and obtain the DC internal resistance data of the battery.

[0071] 3. Negative electrode gram capacity test: Use powder to make button batteries, use metallic lithium as the negative electrode, and charge at 0.1C to 1.5V gram capacity.

[0072] 4. Battery cycle test: The battery is tested under the conditions of 25℃ and 1C / 1C charge and discharge, using the Blue Electric test system.

[0073] 5. Calculation of fast charging capacity: Through the charging of three-electrode batteries at different rates and the negative electrode potential data, the battery limit charging data curve is simulated and calculated.

[0074] The measurement results are shown in Table 1.

[0075] Table 1 Negative electrode material properties of the embodiments and comparative examples and the results of the assembled battery performance measurements

[0076]

[0077] From the comparison between Example 1 and Comparative Example 1, it can be seen that after copper is coated on the carbon skeleton, the resistivity of the powder is greatly reduced. This is because copper metal has extremely high conductivity. After coating the carbon skeleton, the overall structure becomes a conductive network, which can significantly improve the conductivity. It can also be seen from the internal resistance test of the finished battery that the DC resistance is significantly reduced. Due to the reduction in internal resistance, Figure 2 In terms of the fast charging capacity test shown, the charging safety zone and danger zone are simulated by the extreme charging rate data under different states of charge (SOC). It can be seen that the safety area of ​​Example 1 is significantly larger than that of Comparative Example 1, indicating that the fast charging capacity of Example 1 is significantly improved by depositing a thin layer of copper. In terms of gram capacity, since metallic copper does not provide capacity, the gram capacity of the copper-containing silicon-carbon negative electrode material is slightly reduced. In terms of cycle performance, under the positive effect of the copper conductive network in Example 1, the cycle performance is significantly improved. The main reason may be that metallic copper has good ductility, which can alleviate volume expansion during the cycle, while maintaining the overall electrical connection of the negative electrode material and reducing the irreversible loss of silicon active substances. Example 2 increases the thickness of the metallic copper layer. It can be seen that after the copper layer is thickened, the conductivity of the material and the internal resistance of the battery are significantly improved, but due to the increase in the metallic copper content, the mass content of silicon is reduced, so the overall gram capacity is reduced, but the cycle performance is improved.

[0078] Comparative Example 2 has a higher silicon mass fraction than that of Example 1. It can be seen that when the silicon content is too high, the powder resistance of the material and the internal resistance of the battery increase sharply, which may be because silicon is a semiconductor with poor conductivity. At the same time, as the silicon content increases, although the gram capacity of the battery is significantly improved, the battery cycle performance is significantly deteriorated, which is consistent with the theory. The more silicon, the more lithium can be stored, but the volume of silicon expands greatly, the proportion of the porous carbon skeleton decreases, and the buffering volume expansion effect is weakened, so the cycle performance deteriorates.

[0079] Compared with Example 1, the deposition order of copper and silicon in Comparative Example 3 is different. In Comparative Example 3, silicon is deposited first and then copper is deposited. It can be seen that the powder resistance and the internal resistance of the battery are significantly higher than those in Example 1. After silicon is deposited on the porous carbon skeleton, copper is deposited on the silicon surface. Although the overall conductivity can be improved to a certain extent, the connection between silicon and the carbon skeleton is still a weak conductivity connection. In the entire silicon-carbon composite material, the outermost layer in contact with the electrolyte and other auxiliary materials is the porous carbon skeleton material. Therefore, the overall performance is weaker than that in Example 1, but better than Comparative Example 1 (a group with no conductivity improvement at all).

[0080] Compared with Example 1, the method of depositing copper in Comparative Example 4 is different. Comparative Example 4 adopts the chemical reaction method in the prior art to prepare copper. The deposited copper is mainly accumulated copper particles. The purity and density of copper are worse than those of the vapor deposition in Example 1. It can be seen that its powder resistance and battery internal resistance are higher than those in Example 1, the gram capacity is similar, and the cycle is slightly worse than that in Example 1, but the overall performance is better than that of Comparative Example 1 (the group without conductivity improvement).

[0081] In summary, the new silicon carbon prepared by the present invention through copper film deposition on the carbon skeleton has significantly improved conductivity. After the battery is made, the overall performance is significantly improved. The improvement method is similar to that of traditional silicon carbon, the equipment is highly similar, and it has a high application prospect.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a copper-containing silicon-carbon negative electrode material, characterized in that: The steps include: Using a copper source to perform chemical vapor deposition on the surface of the porous carbon skeleton material, controlling the thickness of the copper deposition layer to be 5-50 nm, and then annealing to obtain a copper-coated porous carbon skeleton material; the annealing temperature is 400-500° C., and the annealing time is 20-60 min; Chemical vapor deposition is performed on the surface of a copper-coated porous carbon skeleton material using a silicon source to obtain a copper-containing silicon-carbon negative electrode material; in the copper-containing silicon-carbon negative electrode material, the mass fraction of silicon is 20-50wt%.

2. The preparation method according to claim 1, characterized in that The particle size of the porous carbon skeleton material is 3-15 μm.

3. The preparation method according to claim 1, characterized in that: The copper source is selected from a copper-containing organic precursor or a copper-containing inorganic precursor.

4. The preparation method according to claim 1, characterized in that: In the step of performing chemical vapor deposition using a copper source, the temperature of the chemical vapor deposition is 200-900° C., and the time of the chemical vapor deposition is 3-100 minutes.

5. The preparation method according to claim 1, characterized in that: In the step of performing chemical vapor deposition using a copper source, a gas flow rate of 1 to 5 L / min is used, the gas includes a vaporized copper source and a carrier gas, and the carrier gas is one or more of hydrogen, argon or nitrogen; and the volume fraction of the vaporized copper source is 85 to 95%.

6. The preparation method according to claim 1, characterized in that: The silicon source is selected from monosilane, disilane or dichlorosilane.

7. The preparation method according to claim 1, characterized in that: In the step of performing chemical vapor deposition using a silicon source, the time of chemical vapor deposition is 0.5 to 5 hours, the temperature of chemical vapor deposition is 300 to 600° C., and the flow rate of the silicon source gas is 1 to 5 L / min.

8. A copper-containing silicon-carbon negative electrode material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.

9. A lithium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The negative electrode comprises the copper-silicon-carbon negative electrode material according to claim 8.

Citation Information

Patent Citations

  • Nano-copper coated porous nano silicon composite material as well as preparation method and application thereof

    CN104979559A

  • Preparation method and application of copper-coated silicon monoxide and carbon composite material

    CN117059768A

  • Nano silicon-carbon composite negative electrode material, preparation method and lithium ion battery

    CN116259738A

  • Negative active material and preparation method thereof, negative pole piece and secondary battery

    CN118472243A